Exploring climate variability in the Mataquito river basin of the Maule region, Chile: a spectral analysis approach - Garces Galvez, Juan Jose (2024)
Ecosystems are regulated by independent factors (climate, material, topography, biota, weather, human activities) and by interactive factors (resource supply, microenvironment, disturbance regime, and types of organisms), with their stability and resilience depending on forces and interactions between negative stabilizing feedback and positive amplifying feedback (Chapin et al., 2011). Human reliance on ecosystem services underlines the need to understand the dynamics of these regulating and driving forces. The climatic variables of most excellent and most significant interest for the study of impacts are those that develop at the lowest levels of the atmosphere (Universidad de Chile, 2006). Indeed, understanding climate variability is fundamental to analyzing the interaction of the natural system and the social system, and interpreting the effects on activities, resources, population health, infrastructure, and services (Ferrelli et al., 2017). To understand the behavior of climate variables, the occurrence and intensity of their variations must be analyzed, depending on their location could be subject to diurnal, annual, or decadal temporal variations. Harmonic analysis allows us to know and represent the fluctuations of meteorological data series, depending on their frequency domain. This type of technique allows us to see separately the contributions of processes that vary at different speeds to a time series (Wilks, 2020). Among this type of techniques, the Fourier.